Ultra-efficient design of robust RS flip-flop in nanoscale with energy dissipation study. Issue 1 (1st January 2017) - Abdullah-Al-Shafi, Md.; Bahar, Ali Newaz
Abstract: By the gradual increasing of the attribute size and energy utilization in VLSI chips the component of energy depleted owing to information forfeiture in irreversible valuations will turn into a crucial drawback in the future. Nano components, particularly quantum-dot cellular automata (QCA), have attained extensive interests for their foremost aspects as contrasted to the typical complementary metal oxide semiconductor (CMOS) circuits. QCA, especially due to its substantial diminution in latency, dimension, and energy utilization of circuits, is counted as a latent substitute for the CMOS technology. In this study, a design of RS flip-flop circuit in QCA is proposed. We review an approach for simplified outline of QCA circuits such that the dimensions and energy depletion are substantively decreased. The designed circuit is carried out using single layer and does not involve any rotated cells which particularly expand the fabrication of the outline. The proposed design is simulated with QCADesigner and energy utilization is estimated using QCAPro tool which is a widespread simulation tool. Assessments specify that the outlined structure significantly reduces the number of cells, extent, and latency and depletes very low power which simplifies the complete circuit manufacture and implementation.